El delito de hostigamiento y la oferta de servicios de telefonía. - Macas Allauca, Edison Geovanny (2023)
In March 2022, several reforms were made to the Organic Integral Penal Code in order to protect the right to personal integrity; harassment was classified as a crime, which is punished with a prison sentence of six months to one year, with the aggravating circumstance that when the victim is part of the priority attention groups, a penalty of one to three years of imprisonment is established. Even though the Constitution of the Republic of Ecuador establishes that the right to personal integrity includes physical, mental, moral, and sexual integrity, the criminal type of harassment is only configured when the perpetrator of the infraction seeks closeness with the victim to be able to cause harm to his physical or sexual integrity; however, it is established that the perpetrator of the infraction can be a natural or legal person, classifying companies within the latter, among which are the telephone operators that constantly verbally and insistently offer the contracting of their services to customers. The acts carried out by the telephone operators at the time of offering the contracting of their services are repeated and insistent; they also cause annoyance, disturbance, and anguish to people; however, they cannot be considered harassment because they do not threaten their physical or sexual integrity; instead, they transgress the psychic and moral intimacy.